2004
DOI: 10.1143/jjap.43.l1459
|View full text |Cite
|
Sign up to set email alerts
|

Emission Enhancement by Excimer Laser Irradiation over a Weblike Carbon Nanotube Layer

Abstract: We construct a kink solution on a non-BPS D-brane using Berkovits' formulation of superstring field theory in the level truncation scheme. The tension of the kink reproduces 95% of the expected BPS D-brane tension. We also find a lump-like solution which is interpreted as a kink-antikink pair, and investigate some of its properties. These results may be considered as successful tests of Berkovits' superstring field theory combined with the modified level truncation scheme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…The CNTs formed a weblike networked structure, and the CNT tips were found throughout the small-mesh network-like structure. 21 The diameter of CNTs was approximately 40 nm. Figure 8 shows the surface flatness of the CNT electrode.…”
Section: Preparation Of Cnt Deposited Lead Framementioning
confidence: 99%
“…The CNTs formed a weblike networked structure, and the CNT tips were found throughout the small-mesh network-like structure. 21 The diameter of CNTs was approximately 40 nm. Figure 8 shows the surface flatness of the CNT electrode.…”
Section: Preparation Of Cnt Deposited Lead Framementioning
confidence: 99%
“…Chiral separation techniques such as selective chemistry, gel chromatography, dielectrophoresis, selective oxidation, ultracentrifugation and DNA wrapping chromatography have proven successful yet laborious. 28 On the other hand, metallic tubes can be laser-removed from the mix of chiralities in logic gates, leaving only switchable semiconducting tubes; 27,29,30 semiconducting tubes can be laserremoved, leaving only metallic tubes for metal matrix composites and contacts; 27 the eld emission in CNT mats and powders can be enhanced with laser radiation for screens, improving uniformity and turn-on voltage; 31,32 the tensile strength of CNT threads can be boosted by triggering tube-interlinking, chemically or with electron radiation, which improves load transfer; 33,34 nally, fully analogous to CNTs due their sp 2 carbon, the electrical conductivity in graphene inks can be improved by laser radiation. 35 2 Materials and methods…”
Section: Introductionmentioning
confidence: 99%
“…10͒ are notable because CNTs, and other forms of carbon are characterized by an absorption spectrum having a broad Mie resonance centered near 248 nm ͑5 eV͒. 11 Yotani et al 12 and separately Singh et al 13 showed previously that multi-walled carbon nanotubes ͑MWCNTs͒ are structurally modified by exposure to 248 nm laser light. Separately, Hurst et al 9,10 made the distinction that not all by-products of arc discharge are destroyed at the same rate.…”
Section: Introductionmentioning
confidence: 99%